Biological effect of 1-dodecanol in teneral and post-teneral Rhodnius prolixus and Triatoma infestans (Hemiptera: Reduviidae) - Mougabure Cueto, Gastón Adolfo (2005)
Topical application of 1-dodecanol was significantly more toxic against teneral first nymphs (1-3 h old) than post-teneral first nymphs (24 h old). The lethal dose ratios were 711, 500 for Rhodnius prolixus and 3613 for Triatoma infestans. No significative difference between LD50 was found when 1-dodecanol was injected in recently hatched adult R. prolixus (1-4 h old) nor in older adults (24 h old). These values were similar to those calculated for deltamethrin (an effective triatomicide), showing that 1-dodecanol had no insecticidal properties when it was applied by injection. Topical application of high dose of 1-dodecanol (1 μg/i) on teneral first nymphs of R. prolixus, produced an interruption of the darkening process of the cuticle, and probably in the development of its physiological properties.